Studi Kualitatif tentang Kebutuhan Pembelajaran Guru dalam Peningkatan Profesionalisme di Sekolah Dasar - Amalia, Dina Sustika; Sinurat, Oktavia; Iryani, Eva (Lentera: Jurnal Ilmiah Kependidikan, 2025)
This study aims to determine the needs of teachers in improving their professional performance in elementary schools. This study uses a descriptive qualitative approach, collecting data through in-depth interviews, direct observation, and document review. The data obtained are then analyzed using the Miles and Huberman model, namely by reducing data, presenting data, and drawing conclusions. The research findings indicate that elementary school teachers need training that is more tailored to real-world classroom needs, particularly in using digital media, implementing active learning methods, and conducting more realistic assessments. The results of this analysis provide an important basis for designing appropriate professional development programs according to the current situation and challenges of education.